Strategi Packaging and Programming Paket Wisata untuk Meningkatkan Kunjungan Wisatawan di Taman Kakao Cokelat Desa Banjaroya - Basuki, Ellen Aurelie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Banjaroya village, Kulon Progo regency has a lot of tourism potential, one of the highlights is Cocoa Chocolate Park. As an educational tourist attraction based on agro-tourism, Chocolate Cocoa Park serves several activities offered by tourists related to cocoa cultivation and chocolate production. But in this case, the Cocoa Chocolate Park has not packaged and mammograms such activity services well. The results showed that there are several things that must be improved in packaging and providing programs in the Cocoa Chocolate Park education package. The trick is to save on tour packages need to display the itinerary so that tourists feel easy and can set the time to follow these activities. Then the programming is by grouping the activities offered according to the focus of each field of activity so that tourists can choose the focus of what activities they want to participate in.